Thermal stability and thermal fatigue resistance improvement of new high toughness 5% Cr hot working die steel - Yingnan Di; Dangshen Ma; Hongxiao Chi; Jinbo Gu; Bo Fu; Jian Zhou (Journal of Materials Research and Technology)
This work developed a new high toughness 5% Cr martensitic hot working die steel (GYDCK-20), which exhibits better thermal stability and thermal fatigue resistance than AISI H13 steel. The concrete study involves: conducting on the evolution of microstructures and mechanical properties of two steels during the 60-h holding process at 600 °C, as well as the thermal fatigue behavior under the cyclic heating-water quenching conditions. The experimental results showed that in the case of ensuring the same initial hardness of two steels (43–43.5 HRC), GYDCK-20 emerged better thermal stability and superior toughness after 60-h holding process at 600 °C. After thermal cycling was increased from 1000 to 2000 times, the average crack length growth rate of GYDCK-20 was 31.8% lower than that of H13 and the maximum crack width growth rate was 35.1% lower than that of H13. It was found that thermal fatigue cracking was dominated by transgranular propagation at lower cycle numbers, while more inclined to propagate along the grain boundaries at higher cycle numbers. The higher toughness of GYDCK-20 steel promotes the dispersion of thermal stress, thereby enhancing the thermal fatigue resistance. It is mainly attributed to the lower V content of GYDCK-20 steel, which reduces the density of large-sized MC primary carbides. On the other hand, the lower Si content promotes the dissolution of cementite particles, and the secondary carbides precipitate in a smaller and uniformly distributed form, which hinders the propagation of thermal fatigue cracks, while also delays the coarsening of the fatigue-adverse phase M23C6 carbides.